Peta Resiko Fraud Pengadaan Barang dan Jasa Pemerintah - Mustofa Kamal (Jurnal Transformasi Administrasi, 2019)
This study aims to analyze and provide examples of fraud risk mapping in government goods / services procurement through literature studies, normative studies and prospective and retrospective case studies. An assessment of the likelihood scale for government procurement fraud risk was obtained through a prospective study in previous research. This research assesses the scale of the impact of procurement fraud risk using 2 methods, namely prospective surveys and retrospective case studies. There were 33 respondents in the form of procurement stakeholders who assessed the scale of risk impacts in a prospective survey. The value of procurement fraud risk is obtained by multiplying the scale of likelihood in previous research and the scale of impact in this research. Then the impact scale of the prospective outcome is validated with a retrospective study based on corruption cases at the KPK so that the value of the risk of validated procurement fraud is obtained. The results show a list of risk ratings with the highest risk is that planning does not match the actual needs with a risk level value of 8.76 fromthe results of a prospective survey, and 14.60 from the results of a retrospective analysis. PBJP fraud risk map can be made through a risk analysis matrix with the results of 2 risks entering a high level with priority handling of the 5th, the remaining 56 enter the moderate level, consisting of; 18 risks in the 9th priority priority, 3 risks in the 11th priority priority and 35 risks in the 14th priority priority. The two highest risks are that planning is not according to real needs and planning is tailored to the wishes of certain parties.